Microstructure regulation and fabrication of epoxy-based conductive films with excellent electrical and thermal conductivity, adhesion, toughness, and flexibility - Hongming Yang; Li Zhang; Rong Chen; Shaoyun Guo (Polymer Testing)
The electrically conductive adhesive films (ECAFs) are new materials used for large-format bonding in microelectronics packaging. However, improving its electrical and thermal conductivity, adhesion, and flexibility simultaneously has been a challenge. In this study, silver powder with different particle sizes and poly(3,4-ethylenedioxythiophene)/poly(styrene sulfonate) (PEDOT/PSS) were used to create a high-efficient multi-scale conductive bridge structure. This reduced the volume resistivity from 7.30 × 10−4 Ω cm to 3.80 × 10−4 Ω cm, with lower silver powder content. The thermal conductivity improved from 9.074 W/m·K to 9.124 W/m·K, and adhesion performance between the epoxy matrix and the metal increased from 6.85 MPa to 8.08 MPa. Furthermore, the addition of hydroxyl-functionalized polyurethane materials enhanced the toughness without significantly affecting its electrical, thermal, and adhesion properties. This study successfully prepared epoxy-based conductive adhesive films with a combination of electrical conductivity, thermal conductivity, adhesion, and flexibility, while significantly reducing costs due to the reduction in silver powder content.